The Effect of Labor, Private Investment and Government Investment on Productivity in the Industrial Sector - Arfah, Aryati (Golden Ratio of Social Science and Education, 2021)
This research was conducted with the objectives is to determine the effect of labor, private investment, government investment on production in the industrial sector. Data collection was carried out at the Regional Financial Management Agency Office. The data used in this study is secondary data, namely data on the number of workers, private investment, and government investment. As well as data on the amount of production in the industrial sector within ten years is analyzed and processed by the multiple linear regression method, using the SPSS version 22 program. The results of this study indicate that: (1) labor has a positive and significant influence on production in the industrial sector; (2) private investment has a positive and significant impact on production in the industrial sector; (3) government investment has a positive and significant impact on production in the industrial sector. This shows that production activities in the industrial sector in Sidenreng Rappang Regency rely on labor, private investment, and government investment to continue to increase production capacity. Government investment is a variable that is rarely examined, especially related to production. The government is one of the parties that play an essential role in supporting economic activities in the region.